(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Rotating spiral contacting is a novel technology that allows an excellent control of contacting between two or more phases flowing countercurrently through spiral channel. This method solve the issues can arise from mixing fluids by using the centrifugal effect to enforce the fluids to flow side by side in a narrow channel in parallel layers without mixing. In this work the wide channel model was used to identify the design parameters for a research prototype rotating spiral contactor, and examine the performance within a wide range of operating conditions. The study included air – water system and started by selecting the optimum liquid layer thickness,  , that lead to optimum specific throughput, * N  , and the appropriate molar flow rate ratio, n q for absorption process. Drawing the design envelope for pressure difference as a function of channel height was the best way of selecting the appropriate channel height, h , and also study the effect of using different values of spiral angle, R sin . This later allow of selecting the suitable value of the distance between channel revolutions, t . Finally, this work presents the effect of using wide range of solute values, f ’ on the pressure difference, phases flow rates, and the rotation rate for fixed design parameters of a research prototype.